Water mites of the genus Torrenticola Piersig, 1896 (Acari, Hydrachnidia, Torrenticolidae) from Iran, with description of two new species - Pesic, Vladimir; Saboori, Alireza; Asadi, Mahdieh; Vafaei, Reza; Sanatgar, Elham (Zootaxa, 2006)
Nine water mite species of the genus Torrenticola Piersig, 1896 are reported from Iran. Torrenticola irana and T. khorassanula are described as new to science, and the first records for Iran are given for T. brevirostris (Halbert, 1911), T. barsica (Szalay, 1933), T. amplexa (Koenike, 1908) and T. thori (Halbert, 1944).